Adenovirus sensing by the immune system - Atasheva, Svetlana (Curr Opin Virol, 2016)
The host immune system developed multiple ways for recognition of viral pathogens. Upon disseminated adenovirus infection, the immune system senses adenovirus invasion from the moment it enters the bloodstream. The soluble blood factors, FX, antibodies, and complement, can bind and activate plethora of host-protective immune responses. Adenovirus binding to the cellular β3 integrin and endosomal membrane rupture trigger activation of IL-1α/IL-1R1 proinflammatory cascade leading to attraction of cytotoxic immune cells to the site of infection. Upon cell entry, adenovirus exposes its DNA genome in the cytoplasm and triggers DNA sensors signaling. Even when inside the nucleus, the specialized cellular machinery that recognizes the double-strand DNA breaks become activated and triggers viral DNA replication arrest. Thus, the host employs very diverse mechanisms to prevent viral dissemination.